Evaluation of on-site logistics at different types of construction projects - ANDERSSON, ALBERT; VAN HEEK, OSCAR (My University, 2023)
There is a reduced level of attention to logistics in the construction sector according to the literature. Even though studies have shown that improved logistical measures have provided benefits it is still not implemented at a large scale across the sector. Consequently, the same challenges can be found across projects. The aim of the thesis is therefore to find out if a set of solutions can be found to solve multiple logistical challenges in construction projects. This was done by first performing an empirical and literature background study to find out what challenges exist in construction projects. In the empirical study, four ongoing construction projects, with different characteristics, were scrutinized. It was found that all sites had challenges regarding the handling of deliveries to the construction site and material handling. As an example of this, all sites reported that there was no system to, for instance, keep track of when deliveries had arrived, where they had been placed, and what they contained. After these challenges had been identified through a systematic analysis, possible solutions were explored. In total, three solutions were studied and included the services provided by TPL providers Myloc and Qlocx as well as the implementation of a logistics plan. With the aim of investigating applicability, the solutions were then presented back to the case company. The study concluded that these solutions would be applicable in practice and provide value to many of the case companies' projects. By adding accessible information to the material flow and providing certainty of when and where material is being delivered the TPL services proved valuable to solve challenges regarding coordination and planning. Further, the CLP was deemed a good tool to initiate projects to organize and structure the intended flow of logistics at construction sites. By documenting the logistical setup, the organization can take steps towards standardizing logistics methods across their future projects.
Keywords: Construction logistics, supply chain management, challenges, solutions